Determining the Relationship between Transport Infrastructure and Employment: An Evidence from the Chinese Inland Provinces under the “One Belt, One Road” Initiative - Li, Jin-Hui; Rim, Gwang-Nam; An, Chol-Ju (Modern Perspectives in Economics, Business and Management Vol. 2, 2021)
This chapter discusses the relationship between transport infrastructure and employment in the Chinese inland provinces directly affecting by “One Belt, One Road” initiative. Authors analyzed the relationship between railways and highways - two key elements of transport infrastructure and employment in five Chinese inland provinces directly affected by “One Belt, One Road” initiative. The data were collected from the National Bureau of Statistics of China and some databases related to “One Belt, One Road” for the period of 2008-2017. Descriptive statistics and graphic description approach were used to ensure the comparability of calculation among provinces and to analyze the data. The findings are that there are unclear relationships between transport infrastructure and employment, there exists a positive effect of transport infrastructure on employment in some provinces or not in other provinces over certain period of time, and therefore, improvement of transport infrastructure as well as other relevant factors should be considered for generating employment in the provinces under study.